How well do UK Publishers of Marketing Textbooks Investigate and Understand the Market to which they are Selling? - Masikunas, George; Baverstock, Alison Mary (International Journal of the Book, 2011)
The authors of this paper teach at the Kingston Business School where the number of under-graduates taking an introductory module in marketing at the university and its partner colleges had risen considerably. Triggered by anecdotal evidence from students, we decided to conduct regular surveys to assess student satisfaction with the main recommended marketing textbook. In turn, this raised the wider issue of an appropriate process for selecting a marketing textbook. A paper presented by the authors to the Academy of Marketing in 2007 offered a model that sought to explain how marketing module leaders select a main recommended textbook. The model was called a 'quasi-buying process' because while the module leader selected the title, the buyers and users were students. For this stage of the research, we undertook interviews with five major marketing textbook publishers to assess the value of the quasi-buying model to them. We discussed the range of products they offer to marketing students at UK higher education institutions (HEIs), and the nature of their interactions with those selecting marketing textbooks in these institutions. We sought to establish how well publishers understand both their market and how their product is received and chosen by the various stakeholders. We found that the model we proposed was seen by them as valuable. Other findings indicated the major trends influencing the textbook publishing industry. It emerged that publishers were strongly oriented towards selling their titles to those influencing textbook choice; that marketing is seen as a sales and PR tool with little use of marketing research. It was also found that supplementary materials accompanying marketing textbooks were perceived as offering a valuable method of product differentiation, and hence could be presented as an additional enhancement of the product, but that the publishers were largely unfamiliar with both how the market used or benefitted from them.